2016
DOI: 10.1038/srep23131
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract-induced p120-mediated NF-κB activation in human epithelial cells is dependent on the RhoA/ROCK pathway

Abstract: Cigarette smoke exposure is a major cause of chronic obstructive pulmonary disease (COPD), but the underlying molecular inflammatory mechanisms remain poorly understood. Previous studies have found that smoke disrupts cell-cell adhesion by inducing epithelial barrier damage to the adherens junction proteins, primarily E-cadherin (E-cad) and p120-catenin (p120). Recently, the anti-inflammatory role of p120 has drawn increasing attention. In this study, we demonstrate that p120 has a role in the cigarette smoke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
3
14
0
1
Order By: Relevance
“…To further study the inflammatory responses, we measured the protein abundance of NF-κB (p50/p105) in both female and male mice. The activation of NF-κB is well documented in different lung injury models [44] including cigarette smoke-induced inflammation, wheras research on e-cig aerosol induced NF-κB activation remains less explored [45][46][47][48]. Although the anti-inflammatory effects (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To further study the inflammatory responses, we measured the protein abundance of NF-κB (p50/p105) in both female and male mice. The activation of NF-κB is well documented in different lung injury models [44] including cigarette smoke-induced inflammation, wheras research on e-cig aerosol induced NF-κB activation remains less explored [45][46][47][48]. Although the anti-inflammatory effects (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To further study the inflammatory responses, we measured the protein abundance of NF-κB (p50/p105) in both female and male mice. The activation of NF-κB is well documented in inflammatory responses, especially in cigarette smoke-induced inflammation, however research on e-cig aerosolrelated NF-κB dysregulation is relatively scarce [42,43]. Interestingly, while the anti-inflammatory effects (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] demonstrated that miR-223 acts as a pro-inflammatory factor in inflammatory bowel disease, a premalignant lesion that can lead to colon cancer, by targeting claudin 8 (CLDN8). Our previous study demonstrated that reduced p120 expression causes inflammation by activating RhoA and regulating NF-κB signaling [ 39 , 40 ]. Inflammation and cancer are inextricably linked, and abnormal inflammatory responses can initiate tumor development.…”
Section: Discussionmentioning
confidence: 99%